The Dark Side of Tobacco Industry's CSR: A Socio-Legal Analysis of the Indonesian Corporate Hegemony Campaign - Auditya Firza Saputra (Indonesian Journal of Law and Society, 2021)
As the only country in the Asia-Pacific region that has not yet accessed the Framework Convention on Tobacco Control (FCTC), Indonesia faced an alarming smoking prevalence rate. The situation has worsened during the COVID-19 outbreak because excessive tobacco smoking behavior increased people’s health vulnerability. Despite the destructive impact, most Indonesian citizens shared a common belief about the tobacco industry's importance to the economy. This paper aimed to seek the primary legal issue to reveal how the hegemony latently operated. It deconstructed the established dogma about the industry's misperceived social reputation that frequently served as justifications favoring the industry. Narratives on economic contribution and the industry’s philanthropic campaigns displayed the industry as the protagonist sector and played a significant role in creating a false public opinion on the tobacco industry's reputation. Using a qualitative socio-legal approach, this paper critically described how the industry used the hegemonic methods manifested in Corporate Social Responsibility (CSR) campaigns, which contradicted the ethical principle to secure its market dominance. As a result, the partial legal approach to tobacco control regarding CSR encountered minimalist market interventions from the government, which emerged as the main causes of such an anomaly. As the tobacco control challenge predictably got more difficult on the verge of an economic downturn, the urgency of accessing the FCTC was highly crucial to saving citizens from the upcoming demographic calamity. KEYWORDS: Tobacco Industry, Business and Human Rights, Corporate Hegemony.